Development of a high-rate scalable readout system for gaseous detectors - Scharenberg, L.; Bortfeldt, J.; Brunbauer, F.; Christensen, M. J.; Desch, K.; Floethner, K.; Garcia, F.; Janssens, D.; Kaminski, J.; Lisowska, M.; Lupberger, M.; Muller, H.; et al. (Journal of Instrumentation, 2022)
The RD51 collaboration developed the Scalable Readout System (SRS) as part of its R & D activities on Micro-Pattern Gaseous Detectors. This common multi-purpose readout system allows to read out small R & D detectors (0.2k channels) up to mid-sized experiments with multiple detectors (2.5k to 5k channels). To cope with increased demands on detectors, electronics and readout speed, a new front-end ASIC-the VMM3a-was integrated into the SRS. This led to the development of a scalable, self-triggered high-rate readout system that provides energy, space and time information of the interacting particles at the same time.
CRIS-Team WoS Importer:2023-02-03